Comparison of serum cystatin C and creatinine based methods in detection of early renal dysfunction in critically ill patients - Hafez, Mohammed H; Abdelhamid, Yasser M; Ahmed, Asmaa I (African Journal of Nephrology, 2010)
<span style="color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Early detection of renal dysfunction is of importance inthe care of critically ill patients. Cystatin C was proposedto be superior to serum creatinine in estimation of renal function. This work aimed to compare serum cystatin Cto serum creatinine and creatinine based formulae indetection of early decline in renal function at a singlepoint in critically ill patients. Fifty critically ill patientsadmitted to Cairo University Hospitals ICUs - Egypt wereincluded. Patients with chronic renal disease,thyroid disease, malignancy, patients receivingcorticosteroid therapy, with serum creatinine > 1.4 mg/dland patients receiving diuretics or large volumes of IVfluids were excluded. Serum creatinine, serum cystatinC, adjusted creatinine clearance (Adj Ccr), estimatedGFR (eGFR) by modification of diet in renal disease(MDRD), abbreviated MDRD (abb MDRD) andCockcroft-Gault (CG) formulae were measured. Patientswith renal dysfunction (adj Ccr < 80 ml/min/1.73m2)were 26 (52%) in number. Patients with renaldysfunction and high serum creatinine were 12/26(46.2%) while those with high cystatin C were 23/26(88.5%). Cystatin C was found to be significantlycorrelated with serum creatinine, adj Ccr and eGFR by all studied formulae. Using receiver operatingcharacteristic (ROC) analysis; AUC for Cystatin C(0.976) was more than that for eGFR by abb MDRD(AUC=0.839), MDRD (AUC=0.822), CG formulae(AUC=0.808) and serum creatinine (AUC=0.710)respectively. In conclusion; cystatin C was found to bebetter than serum creatinine, eGFR by abb MDRD,MDRD and CG formulae in detection of early renaldysfunction at a single point in critically ill patients.